Comparative Study on Structural Redundancy of Cable-Stayed and Extradosed Bridges Through Safety Assessment of Their Stay Cables. (January 2021) - Ali, Khawaja; Katsuchi, Hiroshi; Yamada, Hitoshi
Highlights: Cable-stayed and extradosed bridges behave structurally different. Deterministic approach alone does not produce a rational and reliable solution. Reliability of stay cables declines considerably at a reduced safety factor. Ultimate strengths of stay cables are more critical than their fatigue strengths. Loss of two adjacent cables can trigger a progressive collapse of entire bridge. Abstract: This study provides new insights into the comparison of cable-stayed and extradosed bridges based on the safety assessment of their stay cables. These bridges are often regarded as identical structures owing to the use of inclined cables; however, the international standards for bridge design stipulate different safety factors for stay cables of both types of bridges. To address this misconception, a comparative study was carried out on the safety factors of stay cables under fatigue and ultimate limit states by considering the effects of various untoward and damaging factors, such as overloading, cable loss, and corrosion. The primary goal of this study is to describe the structural disparities between both types of bridges and evaluate their structural redundancies by employing deterministic and nondeterministic methods. To achieve this goal, three-dimensional finite-element models of both bridges were developed based on the current design guidelines for stay cables in Japan. After the balanced states of the bridge models were achieved, static analyses were performed for different safety factors of stay cables in a parametric manner. Finally, the first-order reliability method and Monte Carlo method were applied to determine the reliability index of stay cables. The analysis results show that cable-stayed and extradosed bridges exhibit different structural redundancies for different safety factors under the same loading conditions. Moreover, a significant increase in structural redundancy occurs with an incremental increase in the safety factors of stay cables.